A Crisis is a Terrible Thing to Waste: Feminist Reflections on the EU's Crisis Responses. (April 2021) - MacRae, Heather; Guerrina, Roberta; Masselot, Annick
As critics are quick to point out, the European Union (EU) has entered the crisis phase of its evolution. It could be argued that crisis management is now the EU's new normal. Dealing with both endogenous (e.g., economic crisis and Brexit) and exogenous crises (e.g., the migrant crisis and COVID-19), the EU is facing a whole new set of challenges that has the potential to destabilize the complex institutional balance that has maintained the process of European integration over the last 70 years. In this environment of rapid responses, gender+ equality has frequently been compromised. As we argue in this article, the implications of this backsliding are grave not only for equality but also for the European Union as a whole. Drawing on Walby's concept of gender regimes and social transformation, we consider current crises and the EU's responses to those crises to highlight potentially dangerous shifts in the European gender regime. With crisis response increasingly supporting a neo-liberal gender regime, the current state of perpetual crisis in the European institutions does not bode well for the future of equality.